Analisis Kemampuan Manajemen Laba Memediasi Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan - Simorangkir, Melyanti; Suhartono, Sugi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This research examines the impact of profitability and leverage on firm value, with earnings management serving as a mediating variable. Grounded in agency and signaling theories, the study employs secondary data from 44 non-cyclical consumer sector firms listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The findings reveal that both profitability and leverage exert a direct, positive, and significant influence on firm value. Furthermore, profitability is found to significantly affect earnings management. However, the results indicate that earnings management does not play a significant mediating role in the relationship between profitability or leverage and firm value.